1996
DOI: 10.1212/wnl.46.1.198
|View full text |Cite
|
Sign up to set email alerts
|

Elevated intracranial venous pressure as a universal mechanism in pseudotumor cerebri of varying etiologies

Abstract: Pseudotumor cerebri (PTC), or idiopathic intracranial hypertension, is a syndrome associated with multiple clinical conditions. We hypothesize that most if not all etiologies result in an increase in intracranial venous pressure as a final common pathway. We studied 10 patients with PTC. Five had dural venous outflow obstruction as demonstrated by venography, and the five remaining patients had normal venous anatomy. Pressure measurements, made during venography in eight patients, all showed elevated pressures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
223
0
12

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(243 citation statements)
references
References 11 publications
8
223
0
12
Order By: Relevance
“…The results of studies by King 12 and Karahalios 13 further support the theory of obstruction in the cerebral venous outflow. The observation of elevated venous pressures confirmed by manometry during cerebral venography in IIH patients suggests that the occurrence of stenosis of cerebral venous sinuses may be associated with the clinical condition.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…The results of studies by King 12 and Karahalios 13 further support the theory of obstruction in the cerebral venous outflow. The observation of elevated venous pressures confirmed by manometry during cerebral venography in IIH patients suggests that the occurrence of stenosis of cerebral venous sinuses may be associated with the clinical condition.…”
Section: Introductionmentioning
confidence: 59%
“…24 On the other hand, results published in recent years, which show clinical improvement in some patients after the reconstruction of the transverse sinus with endovascular stents, reinforce the hypothesis that the stenosis established in the sinus independently causes the venous flow blockage. 13,22 These two alternatives may give rise to similar symptomatology, alone or concomitantly, explaining the variability in outcomes seen on the clinical assessment of patients.…”
Section: Discussionmentioning
confidence: 99%
“…One theory is that the stenosis causes IIH. Angiographic catheters passed into the intracranial venous sinuses through the jugular veins measured elevated intrasinus pressures in many IIH patients 36,40 . Sometimes these high pressures appeared to be secondary to central venous hypertension, but more often they seemed to be the result of stenotic lesions in the lateral sinuses obstructing cerebral venous outflow.…”
Section: Discussionmentioning
confidence: 99%
“…However, lowering the intracranial pressure can result in normalization of venous morphology, suggesting TS stenosis might be induced by IH itself (secondary cranial venous outflow obstruction (CVOO)) 36,37 . This has led one group to propose intracranial venous hypertension as the final common pathway in the etiology of IIH 36 . Riedel et al have shown that CVOO is not a specific feature of patients with IIH but a universal phenomenon in most patients with IH irrespective of the underlying cause.…”
Section: Cross Sectional Mri/ Ct Findings In Iihmentioning
confidence: 99%
“…La presión venosa intracraneal se eleva, contribuyendo a aumentar la presión intracraneal 53,92 . Es un mecanismo a tener en consideración para el manejo de las pacientes obesas (>25 Kg/m 2 ) con STVP e HIC 94 .…”
Section: Patogenia De Las Alteraciones Endocrinológicasunclassified